The Effect Of Social Media Use Intensity And Digital Ethics Education On Cyberbullying Behavior Among Students Of Sman 2 Mesuji Makmur - Luklu'ul Islamiyati; Sakti Cahyo Nugroho; Mamud Adaem; Muhammad Alfi Syahrin (PT. Education Research Center, 2026)
This study examines the effect of social media use intensity and digital ethics education on students' cyberbullying behavior at SMAN 2 Mesuji Makmur. A quantitative correlational approach was employed with 100 students selected through proportionate stratified random sampling using the Slovin formula. Data were collected via a Likert-scale questionnaire and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. Results indicate that social media use intensity has a positive and significant effect on cyberbullying behavior (β = 0.309; t = 3.821; p = 0.0002), meaning higher usage intensity correlates with increased cyberbullying tendency. Digital ethics education has a negative and significant effect (β = −0.429; t = −5.465; p = 0.0000), indicating that stronger digital ethics understanding reduces cyberbullying behavior. Simultaneously, both variables significantly influence cyberbullying behavior (F = 24.721; p = 0.000), explaining 32.4% of its variance. The remaining 67.6% is attributed to other factors such as self-control, peer environment, parental supervision, and empathy. These findings suggest that cyberbullying prevention requires a dual approach: regulating social media usage patterns and systematically integrating digital ethics education into school culture.